Archival Studies in Greece and the Emerging Field of Integrated Information. Issue 6 (31st July 2014) - Giannakopoulos, Georgios A.; Koumantakis, Ioannis
Abstract : Purpose: Literature presents a wide range of perceptions of the term Personal Digital Libraries (PDL). In this paper we examine PDL as a self-archiving approach, mainly based on individuals' activities. The rationale of using PDL and the capabilities that PDL should offer are also discussed. The key questions we focus on are as follows: "What are the critical features of PDL?" and "Are there technologies that enable the implementation/incorporation of such capabilities in a low cost software product?". Design/methodology/approach: We focus on "a user centred view of information process", and examine how PDL could assist individuals to "create, seek, share and manage the life of information" (Foster et al., 2010). The capabilities that PDL should support, and the related technologies, are also discussed. Then we describe experimentation with a prototype implemented and used to clarify our view for the creation of PDL supporting/providing the mentioned capabilities. Finally, further discussion and conclusions are presented. Findings: The technology is mature enough for building up Personal Digital Libraries (PDLs) with the specified features/capabilities. Originality/value: A new perception of the term Personal Digital Libraries is presented. This perception tries to combine the self-archiving approach of information, based on a low-cost tool, and the user-centred approach to manage the "life of information". This type of library is mainly used to cover personal needs. Users benefit from this type of PDL by: (a) personalised handling of information, (b) reduced time to search and seek specific documents in their personal collections, and (c) less possibility for broken links or unavailable documents. We must also mention that new opportunities seem to appear for offering PDL as a service in the cloud.